Friability and its relationship with some physical and chemical soil properties under sugar cane crop - Avila P., Edgar Alvaro; Leiva B., Fabio Rodrigo; Darghan C., Aquiles Enrique (Revista de Ciencias Agrícolas, 2017)
Friability is an important indicator of the physical quality of soils and it is linked to the variability of other edaphic properties. This study aimed to evaluate the relationship between friability and different physical and chemical soil properties cultivated with sugar cane. The sampling was carried out in the first two horizons (Ap and A1) of 91 sites corresponding to five soil orders (Inceptisol, Molisol, Vertisol, Alfisol and Ultisol). Ten aggregates were selected for each of the four ranges (2.0 to 4.79, 4.80 to 9.49, 9.50 to 19.00 and 19.01 to 35.70 mm) that predominated in the 182 horizons. The 7,280 aggregates were dried in a greenhouse and an oven; subsequently, subjected to compression to determine the compressive strength (CS) and the friability index that corresponded to the lower limit (FIi) of the confidence interval of the variation coefficient It was determined the mean weight diameter (WMD), the aggregation state (AS), the bulk density (AD), the total porosity (TP), the Ph, and the electrical conductivity (EC) of the soil samples. In addition, measurements of dispersion and central tendency, three-dimensional surface graphs, and a linear model were used with a completely random design using an incomplete factorial arrangement. No effect was seen from the WMD, AD, pH, or EC on the FIi; however, the AS and the TP had significant effects from the inferential point of view.